Comparison of Hematological Parameters Between First-Episode Schizophrenia and Anti-NMDAR Encephalitis - Huang, Kai; Tang, Yamei; Chen, Zhiheng; Ding, Shan; Zeng, Hongtao; Zhao, Yuxu; Yu, Qi; Liu, Yong (Frontiers in Cell and Developmental Biology, 2022)
Background: First-episode schizophrenia (FES) and anti-NMDAR encephalitis are different disorders with similar psychiatric symptoms, and both diseases are associated with the inflammatory system. In this study, we compared hematological parameters and inflammation ratios in anti-NMDAR encephalitis, FES, and healthy control. Methods: We enrolled 106 patients (53 FES patients and 53 anti-NMDAR encephalitis patients) and 59 healthy controls. The values of the neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), monocyte–lymphocyte ratio (MLR), and systemic immune-inflammation index (SII) were used to evaluate inflammation. Other parameters such as the white blood cell (WBC), platelet (PLT), uric acid (UA), total bilirubin (TBIL), total bile acid (TBA), and serum albumin counts were also used to compare inflammation ratios between these two diseases. Results: SII, NLR, PLR, MLR, and serum albumin levels were statistically significantly different between these three groups (p < 0.05). The values of SII, NLR, PLR, and MLR were significantly higher in the anti-NMDAR encephalitis group than those in the FES group (p < 0.05), and the values in both diseases were more increased than those in HC (p < 0.05). The serum albumin level was significantly lower in anti-NMDAR encephalitis than in FES (p < 0.05). WBC, neutrophil, lymphocyte, and monocyte counts showed significantly higher levels in the anti-NMDAR encephalitis group and FES group separately (p < 0.05). Other parameters like TBA, TBIL, and UA showed no difference between groups. Conclusion: In summary, this is a relatively new study that is innovative by comparing some inflammation markers of peripheral blood in two diseases with clinically psychotic symptoms. These two diseases are related to the inflammatory system, proving that NMDAR dysfunction is related to psychotic symptoms. Besides, NLR, PLR, MLR, and serum albumin can be used as biomarkers to distinguish the two diseases. The serum albumin level in patients with anti-NMDAR encephalitis was lower than that in patients with schizophrenia.